2019
DOI: 10.1021/acs.nanolett.9b02097
|View full text |Cite|
|
Sign up to set email alerts
|

Discrimination of Bond Order in Organic Molecules Using Noncontact Atomic Force Microscopy

Abstract: Noncontact atomic force microscopy (nc-AFM) with a CO-functionalized tip can image submolecular structures through high-resolution images with the possibility of discriminating bond order. We employ real-space pseudopotential calculations to simulate nc-AFM images of molecules containing double (dibenzo­(cd,n)­naphtho­(3,2,1,8-pqra)­perylene (DBNP), hexabenzo­(bc,ef,hi,kl,no,qr)­coronene (HBC)) and triple (1,2-bis­[2-(2-ethynylphenyl)­ethynyl]-benzene (BEEB), 6-phenylhexa-1,3,5-triynylbenzene (PHTB)) bonds. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…[1] The submolecular resolution of organic molecules was achieved by using CO-functionalized tip and qPlus technique. [2,3] The high performance of topography imaging enables its application in atomic recognition, [4,5] surface manipulation, [6,7] bond order recognition, [8][9][10] self-assembly, [11] and tracing reactions on surfaces. [12] The terminating CO molecule is chemically inert, which reduces the manipulation or bonding with the sample molecule.…”
Section: Introductionmentioning
confidence: 99%
“…[1] The submolecular resolution of organic molecules was achieved by using CO-functionalized tip and qPlus technique. [2,3] The high performance of topography imaging enables its application in atomic recognition, [4,5] surface manipulation, [6,7] bond order recognition, [8][9][10] self-assembly, [11] and tracing reactions on surfaces. [12] The terminating CO molecule is chemically inert, which reduces the manipulation or bonding with the sample molecule.…”
Section: Introductionmentioning
confidence: 99%
“…It uses the tip and sample charge densities and the sample electrostatic potential obtained from density functional theory (DFT) calculations as input. Then just two fitting parameters are used to reproduce tip-sample forces retaining DFT accuracy, similarly to other purely first-principles methods [34,35]. The resulting model is able to efficiently compute HR-AFM images, enabling extensive exploration of atomic scale structure and interpretation of the measured images.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Since then, extending nc-AFM to characterize molecular structures, specific chemical bonds and atomic species remains an ongoing challenge for researchers. [2] Numerous studies [3][4][5][6][7][8] have demonstrated that nc-AFM has the capability to discriminate carbon-carbon bond order, bond length, and molecular adsorption geometry on various substrates. With respect to the identification of atomic species, previous work [9][10][11][12] has shown the possibility of discriminating atom species under certain conditions.…”
Section: Introductionmentioning
confidence: 99%